2010
DOI: 10.1099/ijs.0.011809-0
|View full text |Cite
|
Sign up to set email alerts
|

Basfia succiniciproducens gen. nov., sp. nov., a new member of the family Pasteurellaceae isolated from bovine rumen

Abstract: Gram-negative, coccoid, non-motile bacteria that are catalase-, urease- and indole-negative, facultatively anaerobic and oxidase-positive were isolated from the bovine rumen using an improved selective medium for members of the Pasteurellaceae. All strains produced significant amounts of succinic acid under anaerobic conditions with glucose as substrate. Phenotypic characterization and multilocus sequence analysis (MLSA) using 16S rRNA, rpoB, infB and recN genes were performed on seven independent isolates. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 31 publications
0
64
0
Order By: Relevance
“…Each of the two subclades has its own distinct USS, the Hin type and Apl type, respectively, and the species of each subclade preferentially take up DNA containing the corresponding USS (33). Gallibacterium is positioned as the deepest branch in Pasteurellaceae phylogenies and thus is a sister group to the rest of the Pasteurellaceae and not a member of either subclade (22,23).…”
Section: Identification Of a Putative Competence Regulon In G Anatismentioning
confidence: 99%
“…Each of the two subclades has its own distinct USS, the Hin type and Apl type, respectively, and the species of each subclade preferentially take up DNA containing the corresponding USS (33). Gallibacterium is positioned as the deepest branch in Pasteurellaceae phylogenies and thus is a sister group to the rest of the Pasteurellaceae and not a member of either subclade (22,23).…”
Section: Identification Of a Putative Competence Regulon In G Anatismentioning
confidence: 99%
“…4) (73, 116). G. anatis represents an outgroup of the two main subclades (117,118), suggesting that this species would be an ideal system for investigation of the origins of uptake bias and uptake sequence accumulation. In contrast, Haemophilus ducreyi (Apl-USS subclade) has a substantially lower density of USS than other Pasteurellaceae, suggesting either that it has lost competence or that its uptake specificity is changing (Fig.…”
Section: Figmentioning
confidence: 99%
“…Comparative genomic and phylogenetic analyses of the Pasteurellaceae have revealed that many members of this highly diverse family were poorly classified (54, 56). Indeed, a number of the Pasteurellaceae have already been renamed: Histophilus somni (formerly Haemophilus somnus, H. agni, and H. ovis) (57), Mannheimia (formerly Pasteurella) haemolytica (58), Bibersteinia (formerly Pasteurella) trehalosi (59), Actinobacillus (formerly Haemophilus) pleuropneumoniae (60), Actinobacillus (formerly Pasteurella) ureae (61), Aggregatibacter (formerly Actinobacillus) actinomycetemcomitans (62), Aggregatibacter aphrophilus (formerly Haemophilus aphrophilus and H. paraphrophilus) (62), Aggregatibacter (formerly Haemophilus) segnis (62), Avibacterium (formerly Haemophilus) paragallinarum (63), Avibacterium (formerly Pasteurella) gallinarum (63), Avibacterium (formerly Pasteurella) volantium (63), Avibacterium (formerly Pasteurella) avium (63), Basfia (formerly Mannheimia) succiniciproducens (64), and Gallibacterium (formerly Pasteurella) anatis (65). However, as can been seen from the 16S rRNA phylogenetic tree shown in Fig.…”
Section: Pasteurella and The Pasteurellaceae Family Comparative Genommentioning
confidence: 99%